MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA KELAS VIII MTSN 2 MEDAN - Munawaroh, Sya’adatul; Lubis, M Rajab (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
The purpose of this research was to improve the interpersonal communication skills of students through group counseling using techniques sociodramas. The method used is PTBK (Action Research Guidance and Counseling) with two cycles consisting of four stages, namely planning, action, observation, and reflection. The subjects were 9 students of class VIII-7. From the analysis of data obtained by 5 students who have low interpersonal communication skills and 4 students have moderate interpersonal communication skills. After the first cycle measures an increase of 5 studentscommunication skill into high degree of interpersonal communication skills, 4 students have enough interpersonal communication, and only 1 have low interpersonal communication (76%). After the second cycle of improvement also happens to 8 students into high degree of interpersonal communication skills and only one student has moderate level of interpersonal communication (86%). The results of this study showed that group counseling sociodramas technique can improve interpersonal communication skills of students.Keyword: Group Counseling, Sosiodrama Technique, Life Skill Problem